Dichlorvos (2, 2-dichlorovinyl dimethyl phosphate DDVP (SNIPER)) Toxicity on Histological Organs of Wistar Rats Fed on Treated Cowpea Grains (Vigna unguiculata (L.) Walp) - Fayinminnu, Olajumoke O.; Adebimpe, Rofiat M.; Adebiyi, Opeyemi E.; Oshoke, Frankly I. (Journal of Agricultural Studies, 2022)
Cowpea is an important grain legume that provides half of the plant protein and is consumed worldwide. The crop is usually affected by pests on the field and in storage which always result in huge losses, hence being controlled by using synthetic pesticides. However, consumption of cowpea grains treated with synthetic pesticides had resulted in bioaccumulation and several health-related problems. Therefore, this study examined the toxic effects of Dichlorvos (DDVP) treated cowpea grains fed to Wistar rats for four weeks. Sixteen male rats weighing 125±20g were used for this experiment. They were randomly divided into four groups of four rats each including the control and acclimatised for one week fed with Standard Feed Ratio (SFR). The DDVP (98% purity) was applied at the rates of 0 (control), 0.23, 0.33, and 0.43mL/kg directly to 1kg cowpea grains of IT 89k-391, respectively. Treated cowpea grains were milled (with a 2 mm sieve) and mixed with SFR and fed to the animals daily for four weeks. Data were collected weeks after treatment (WAT) on feed intake, body weight gain/loss, hematology, and, serum chemistry and analysed using ANOVA at p<0.05, while histopathology was examined. Results showed significant differences (p < 0.05) in all the parameters. There was a reduction in feed intake and body weights progressively in DDVP cowpea treated animals, while the control animals increased. Hematological parameters showed 0.23 mL/kg DDVP recording the highest hemoglobin (g/dl) (17.00±1.16), while the lowest value in white blood cells (1100±5.78 x 103/µL), and 0.43 mL/kg recorded the lowest and highest red blood cells (103/µL) (5.34±0.78) and (8.83±0.23) all between 1 and 4 WAT. Serum parameters revealed Total protein having lowest values (5.22±0.01, 5.13±0.01, 5.18±0.01) from 0.23, 0.33, and 0.43 mL/kg DDVP treated animals. Alkaline phosphate, Aspartate aminotransferase, and Alanine transaminase recorded the highest values from 0.43 and 0.33 mL/kg treatments at 3 and 4 WAT, respectively. Histopathology at 1 to 4 WAT revealed capillary congestion with necrotic changes, severe cell infiltration of interstitial and parenchyma with inflammatory cells in the kidneys of 0.23, and 0.33 mL/kg DDVP cowpea fed animals. On liver organs, 0.23, 0.33, and 0.43 mL/kg treatments showed necrosis, vacuolar degeneration of hepatocytes, and congestion with distinct cysts and granular formation. The central portions of livers were pale and distinct patterns of arrangement in cords were absent. However, the control animals recorded the highest values in the aforementioned parameters with clear and normal liver and kidney organs in the experiment. In this study, varied changes observed on the hematological, serum biochemical, and histopathological parameters at 0.23, 0.33, and 0.43 mL/kg dichlorvos (DDVP) treated cowpea grains could result in impairment of vital organs, hence ill health issues. Continued use of dichlorvos for cowpea grains in preservation should be discouraged to prevent health problems and promote high-quality nutrition and safe food.